Resettlement and Nutritional Implications: the Case of Orang Asli in Regroupment Schemes - Lin, Khor Geok (Universiti Putra Malaysia Press, 1994)
Since the mid-1970s, increasingly more Orang Asli from the interior have been relocated into regroupment schemes, where they are introduced to the cultivation of cash crops including rubber and oil palm. This involves a major change to their socia-economic lifestyle, in having to switch from subsistence cropping coupled with hunting-gathering activity to being drawn into the market economy. Some 15 years after relocation, the nutritional status of Orang Asli children in regroupment schemes can be described as poor with a moderate to high prevalence of underweight, acute and chronic malnutrition. Their dietary intakes are deficient in calories and several major nutrients. This article also presents findings of the deleterious impact of resettlement on nutritional status experienced in other countries. There exists an over-simplified assumption that introduction to cash cropping will lead to increased income, which will provide more money for food, and in turn result in improvement in nutritional status. Evidence involving indigenous groups and peasant farmers is provided to show that this linkage does not necessarily emanate. In reality, relocation entails cultural uprooting and lifestyle changes which may not be overcome by the provision of physical facilities and economic incentives only.